PENGARUH MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP PENINGKATAN KETERAMPILAN GERAK SHOOTING DALAM PERMAINAN SEPAK BOLA - Abdul Sukur; Agi Ginanjar; Mochamad Zakky Mubarok (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Team Games Tournament (TGT) learning model on improving shooting movement skills in football. The research employed an experimental design. The population consisted of 25 students, and the sample was selected using a purposive sampling technique. The research findings show that the average pretest score was 4.52, while the average posttest score increased to 8.12. The standard deviation for the pretest was 1.12, and for the posttest was 1.30. The variance values for the pretest and posttest were 1.26 and 1.69, respectively. The normality test results indicate that the pretest data had a significance value of 0.07, which is greater than 0.05, indicating that the data were normally distributed. Similarly, the posttest data obtained a significance value of 0.12, which is also greater than 0.05, confirming normal distribution. Furthermore, the hypothesis test yielded a significance value of 0.00, which is less than 0.05, indicating a statistically significant effect. Therefore, it can be concluded that the Team Games Tournament learning model has a significant effect on improving students’ shooting movement skills in football.